Computer-aided weaving: from numerical data to algorithmic textiles - Koutsomichalis, Marinos; Psarra, A (My University, 2015)
Contemporary computers are direct descendants of the Jackard's loom-an industrial era machine that used punched cards as a way of calculating and representing numerical data to be subsequently transformed into weaving patterns (Essinger 2004)-and of Babbage's Analytical Engine, which employed a variation of the same system to perform complex probabilistic calculations (Swade 1991). In that vein, Ada Lovelace foresaw the future application of programming as the means to realise computer-generated music and graphics (Charman-Anderson, 2013) and this way prepared the grounds for the entire informational revolution to follow. Weaving is to be understood as a constitutionally algorithmic process, which has henceforth evolved in parallel to computer technology. In that vein, contemporary fabrication tactics, such as those suggested by Hatch (2013), constitute a platform for the further development of new technologies and/or for the re-appropriation of existent ones. A re-conceptualisation of the design process through data visualisation and parametric design schemata is cast possible this way (Romano & Cangiano 2014, pp. 170--172).